What millennials want from work : how to maximize engagement in today's workforce - Deal, Jennifer J.; Levenson, Alec Robert, 1966- (McGraw-Hill Education, 2016)
Based on fieldwork and survey data from global research on more than 25;000 Millennials and 29;000 older workers in 22 countries; this essential book explains who Millennials really are; and offers practical advice to help those who manage; lead; and work with Millennials to improve teamwork; increase productivity; strengthen organizational culture; and build a robust talent pipeline. --